Needs Assessment Knowledge from Facilitator of Community Empowerment Program in the Digital Era - Purnomo, Purnomo; Hufad, Achmad; Wahyudin, Uyu; Akhyadi, Ade Sadikin; Lutfiansyah, Dadang Yunus (Universitas Negeri Semarang, 2020)
Cadres of Kampung KB as facilitators of community empowerment programs are required to have good knowledge in implementingÂ needs assessmentÂ withÂ adaptiveÂ dataÂ managementÂ with theÂ industrialÂ eraÂ 4.0.Â TheÂ needs assessmentÂ technique isÂ not only doneÂ manually but can use digital technologyÂ toÂ facilitate data collection and data access.Â However, the use of technology needs to be supported by the facilitator's knowledge of the needâ€™s assessment, because it is the basis for understanding the meaning of data tracing. This study uses a quantitative approach, in the form of descriptive statistics, namely interpreting the percentage data from the answers given by the respondents. From the results of the study, it was found that the cadres' needs assessment ability was included in the â€œEnoughâ€ category, while the competence that needed to be improved was knowledge about setting priority needs. So that the researchers suggest, it is necessary to hold competency training for KB cadres or village administrators which aims to provide understanding and skills in conducting needs assessment.Â